Didactic conditions for creative self-development of future music teachers (on the example of studying the subject “Choral Conducting”) - Кокарева, Елеонора (Pedagogy of Higher and Secondary Education, 2014)
Kokareva E. О. Didactic conditions for creative self-development of future music teachers (on the example of studying the subject “Choral Conducting”). The author highlights heuristic learning as a means of creative self-development of future teachers. The author also substantiates the didactic conditions for creative self-development of students studying at musical faculties on the example of one of the core subjects – choral conducting.